High Potency of SN-38-Loaded Bovine Serum Albumin Nanoparticles Against Triple-Negative Breast Cancer - Hsin-Che Lin; Chih-Hung Chuang; Meng-Hsuan Cheng; Yu-Chih Lin; Yi-Ping Fang (MDPI AG, 2019)
Triple-negative breast cancer (TNBC) is an aggressive type of breast cancer with a worse prognosis than other types. There are currently no specific approved treatments for TNBC. Albumin is a promising biomimetic material that may be fabricated into nanoparticles to possibly exert passive effects on targeted tumors. Irinotecan has been extensively used in clinical settings, although a high dosage is required due to its low efficiency of conversion into the active metabolite SN-38, also known as 7-ethyl-10-hydroxy-camptothecin. The aim of this work was to optimize SN-38-loaded bovine serum albumin nanoparticles (sBSANPs) and evaluate their potency against TNBC. The sBSANPs were characterized by a small size of about 134−264 nm, a negative charge of −37 to −40 mV, an entrapment efficiency of 59−71%, and a particle yield of 65−86%. The cytotoxicity assays using sBSANPs showed a higher potency specifically against both MDA-MB-468 and MDA-MB-231 cells (ER−, PR−, HER2−) compared to MCF-7 (ER+, PR+, HER2−), and exhibited an extremely low IC50 at the nanomolar levels (2.01−6.82 nM). The release profiles indicated that SN-38 presented an initial burst release within 12 h, and sBSANPs had a slow release pattern. Flow cytometry results showed that the fluorescence intensity of sBSANPs was significantly higher than that of the control group. The confocal images also confirmed that sBSANPs were taken up by MDA-MB-468 cells. Moreover, we found that a larger BSANP size resulted in an increased hemolytic effect. In vivo animal studies demonstrated that loading of SN-38 into bovine serum albumin nanoparticles could minimize the initial concentration without extending the elimination half-life, but significantly minimized the Cmax (p < 0.001) as compared with irinotecan treatment.